Possibilities of Creating a Mechanism on FDM 3D Printer - Strnad, Jan; Reznicek, Martin; Jelinkova, Kristyna; Janostik, Vaclav; Ovsik, Martin (Manufacturing Technology Journal, 2019)
The article deals with additive manufacturing technologies especially with ability to create reports on FDM 3D printers. These assemblies are non-disambiguable. Therefore, it is important to choose the optimal magnitude of the deviation between the walls so that the mechanism has the required mobility. These deviations are examined in several materials with different rheological properties. Finally, the dependence of the magnitude of the variance between the walls and the thickness of the layer for the given materials is shown. The result is the recommendation of modelling and printing parameters.
Keywords: FDM; 3D print; deviation; model; parameters